Analisis Pelaksanaan Kurikulum 2013 Pada Mata Pelajaran Ekonomi SMA Berakreditasi A Di Kota Solok (Studi Kasus Pada SMA N 4 Solok) - Sri Wahyuni; Tri Kurniawati (Universitas Negeri Padang, 2019)
One element of change in the 2013 Curriculum is a process standard that contains minimum standards regarding planning, implementation, and assessment of the learning process. Researchers conducted research on the analysis of the implementation of the 2013 curriculum in economics subjects of A Accredited High School. The purpose of this study was to find out and analyze the implementation of the 2013 Curriculum at SMA N 4 Solok in terms of process standards. This research uses a descriptive method. This research was conducted at Solok Public High School 4 in the first semester of the 2019/2020 school year. This study analyzes the learning tool document developed by the economics teacher and the implementation of learning in the classroom. Data collection techniques namely documentation, interviews, and observation. Data analysis techniques use inductive analysis techniques, including data collection, data reduction, data presentation, and drawing conclusions. The results showed, 1) In general, the learning tools developed by the economics teacher were already good, but the contents still seemed incomplete in accordance with Permendikbud No. 22 of 2016. 2) The implementation of learning in accordance with the 2013 curriculum has not been implemented optimally, especially in using scientific approaches and learning methods. 3) The assessment of the economic learning process has not been carried out in accordance with Permendikbud No. 22 of 2016, because teachers are seen to only conduct assessments based on knowledge, this is due to limitations in the development of assessment instrumeKeyword: Process Standards and 2013 Curriculum